Biodiversity effects of the Russia–Ukraine War and the Kakhovka Dam destruction: ecological consequences and predictions for marine, estuarine, and freshwater communities in the northern Black Sea - Kvach, Yuriy; Stepien, Carol A.; Minicheva, Galyna G.; Tkachenko, Pavlo (Ecological processes, 2025)
Background The effects of war on biodiversity, habitats, ecosystem services, and water, seafood, and fishing resources are complex and long-lasting, yet their ongoing environmental analyses are limited. The Russia–Ukraine War (2022–present) comprises a unique ecological situation to examine biodiversity effects on the distinctive cold-temperate northern Black Sea ecosystem, which has an intriguing biogeographic history and high endemism resulting from geographic isolation and differentiation. Results We summarize negative and positive effects from the War on the aquatic (marine, estuarine, and freshwater) biota and their habitats, focusing on investigations by the Institute of Marine Biology, National Academy of Sciences of Ukraine. Negative effects include toxins and habitat damage from oil spills, shelling, mining, explosions, flooding, and fires; along with disregard of Protected Areas. Positive effects are reduced anthropogenic loads from less shipping, fishing, trawling, recreation, hydraulic engineering, construction, and tourism. The Kakhovka Dam’s destruction on June 6, 2023 was the greatest ecological catastrophe to date, causing extensive downstream flooding with freshwaters and pollutants that destroyed many populations and habitats. We discern that many effects have been temporary, with habitats and species replenishing, and some reverting to their historical biota characteristic of lower salinity regimes. However, significant habitat destruction, disturbances, and pollutant damages remain. Since many of the native species evolved in conditions favoring broad salinity, temperature, and oxygen tolerances, the northern Black Sea ecosystem appears pre-adapted for ecological recovery and persistence, which may equate to ecological resilience during and after the War. Conclusions The native biota exhibits long-term adaptiveness to marked salinity and temperature fluctuations, alongside a background of invasive species. An evolutionary and recent history of broad environmental tolerances by a large proportion of Black Sea species may enhance their ability to withstand marked environmental changes, including habitat destruction, as during the Kakhovka Dam's breakage and other stressors that continue during the Russia–Ukraine War. The Black Sea community’s overall ecological resilience is likely to facilitate persistence and adaptation to the War’s effects and the accelerating impacts of climate change, increased global transportation, and invasive species—meriting worldwide conservation agency focus and cooperation.